Towards a Typology of Tafsir Al-Qur`an by Al-Qur`an and by Sunnah; Exegetical Patterns in Aqīdah and Ibādah Verses: دراسة تطبيقية في صور تفسير القرآن بالقرآن وتفسير القرآن بالسنة في آيات العقيدة والعبادة - Lira Erlina (ZAD Al-Mufassirin, 2026)
This study aims to describe the various tafsir of the Qur'an by Qur'an and by Sunnah as applied to verses on Aqidah and Ibadah, while also analyzing their contribution to producing a comprehensive understanding that aligns with Sharia principles. The diversity of interpretation methodologies provides a positive contribution by enriching the treasure trove of Islamic knowledge, but it can also lead to differences in understanding if not based on true methodologies like the Qur'an and Sunnah as primary sources of tafsir. Data was obtained through a descriptive-analytical qualitative approach by analyzing verses on Aqidah and Ibadah using the theoretical foundations of Ulum Qur'an and Usul Tafsir. Research results show that the concrete model of tafsir Qur'an by Qur'an and by Sunnah includes; explanations of the meanings of gharīb words and masyhūr sentences, elaboration (ithnāb) of concise verses (ījaz), answering questions, takhsīs al-‘am, taqyīd al-muthlaq, bayān al-mujmal, explanations of mutasyābihat verses, interpretation with qira`at, and interpretation on the asbāb an-nuzūl, provides a specific, authoritative, and systematic understanding of the tafsir of ayat akidah dan ibadah.